Inability to Utilize Information Technology in Improving The Quality off Government Financial Statements - Pasolo, Fahrudin; Pasolo, Muhammad Ridhwansyah; Ameliana, Yana (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research investigates the factors that influence the quality of government financial statements with organizational commitment as a moderator in Jayapura City, Papua. This research is a quantitative research type. Using 88 samples from 30 regional apparatus organizations within the Jayapura city. We found that Government Accounting Standards, Internal control system, have significant influence on quality of government financial statements. While the use of information technology does not have a significant effect on quality of government financial statements. This study has an important contribution in finding determinants of the quality of financial statements in Jayapura city government and become an evaluation of future improvements.